COVID-19 Lockdown Measures on Least Developing Economies in Africa-a case of Malawi Economy - Munthali, George N. Chidimbah; Xuelian, Wu (Technium Social Sciences Journal, 2020)
The outbreak of COVID-19 pandemic has caused the entire world at standstill affecting all the sectors of economies in the whole world. In order to reduce the spread of the cases and the mortality rate of this pandemics many economies have implemented a lot of social distancing measurers with the aim of separating people direct and indirect contacts as the Virus can be transferred through physical contact and is also an airborne, these isolations measures have proved to be effective in many countries. One of the most measures that the developed and developing economies are using is partial or full lockdown, despite being effective way of reducing the impact of the Virus, lockdown measures has also its own cost that the economies are to bier especially when it’s a total or full countrywide lockdown which policy makers must look into too. The approaches of lockdowns and attitudes of people towards lockdowns has been seen differencing in many countries depending on the political system of the government which is in that jurisdiction economic status of the country. This perspective recommends that Countries like Malawi and any other when implementing these lockdowns measures the authorities should consider the political system, costs and other the measures to carter for helping the people like proving stimulus package in order to have a successfully and effective lockdown which is highly recommended to be an effective way of combating the Virus.